FUNCTIONAL OUTCOME OF DELAYED PRESENTING FRACTURE NECK OF FEMUR MANAGED BY CANNULATED SCREW AND FIBULAR GRAFT - Masroor Ahmed,; Bux, Muhammad; Hussain, Ghulam; Kumar, Mukesh; Ahmed, Naveed (Journal of Ayub Medical College Abbottabad, 2021)
Background: Delayed presenting Fracture neck of femur is one of the complex and challenging fracture to treat. Multiple treatment options are available with varying results. This study was conducted to assess the functional outcome of fracture neck of femur seeking medical attention several days after injury that are managed by cannulated screw and fibular. Methods: A total of 35 patients were included in the cross-sectional study performed at orthopaedic surgery department of United Medical & dental college Karachi. Adults aged 18 years and over both male and female with fracture neck of femur presenting 14 days after the injury for medical treatment were included in the study. Ethical approval was obtained from the ethical review committee and patients who provided written informed consent were included in study. Data analysis was performed through SPSS version 20. Results: Thirty-five patients with fracture neck of femur of both sexes 25 (71.4%) male and 10 (28.6%) females were included in study. out of which 14 (40%) of the patients had sub-capital fracture and 21 (60%) patients had trans-cervical fracture neck of femur. Mean age of patients was 32.14±10.20 years. Twenty-eight (80%) patients out of 35 had excellent and good outcome, 4 (11.4%) cases had fair and 3 (8.5%) had poor outcome Conclusion: Cannulated screw fixation along with non-vascularized fibular graft is effective technique to management of delayed presenting fracture neck of femur as it is easy, inexpensive and does not require any special instrumentation or expertise